Women contributions to open source software innovation: A social constructivist perspective - Mahmod, Musyrifah; Mohd Yusof, Shafiz Affendi; Md Dahalin, Zulkhairi (2010)
The popularity of Open Source Software (OSS) is increasing as a platform for modern software innovation with the prominent concept of “freedom”. Freedom in OSS innovation is similar to freedom of speech not in term of price.However, less than 2% of the contributors are women in OSS innovation. Minorities including women are often ignored in OSS innovation process.The gender issues in OSS innovation might be more complex than what it seems, as female contributors are often experience hybrid discriminations, both from the male dominated OSS community and socio-cultural patriarchy.This paper concerns the questions of how innovation is achieved in open source software communities through social constructionist perspectives focusing on feminist views.